2023
DOI: 10.4236/ojs.2023.133019
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Memory Capacity across Time and Language Estimated from Ancient and Modern Literary Texts. Study-Case: New Testament Translations

Abstract: We study the short-term memory capacity of ancient readers of the original New Testament written in Greek, of its translations to Latin and to modern languages. To model it, we consider the number of words between any two contiguous interpunctions I p , because this parameter can model how the human mind memorizes "chunks" of information. Since I P can be calculated for any alphabetical text, we can perform experiments-otherwise impossiblewith ancient readers by studying the literary works they used to read. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…To model a two-unit STM processing, we further develop our previous studies based on a parameter called the "word interval", indicated by I p , given by the number of words between any two contiguous interpunctions [1][2][3][4][5][6][7][8]. The term "interval" arises by noting that I p does measure an "interval"-expressed in words-which can be transformed into time through a reading speed [9], as shown in [1].…”
Section: Short-term Memory Capacity Can Be Estimated From Literary Textsmentioning
confidence: 99%
See 4 more Smart Citations
“…To model a two-unit STM processing, we further develop our previous studies based on a parameter called the "word interval", indicated by I p , given by the number of words between any two contiguous interpunctions [1][2][3][4][5][6][7][8]. The term "interval" arises by noting that I p does measure an "interval"-expressed in words-which can be transformed into time through a reading speed [9], as shown in [1].…”
Section: Short-term Memory Capacity Can Be Estimated From Literary Textsmentioning
confidence: 99%
“…The presence of interpunctions in a sentence and its length in words are, very likely, the tangible consequence of two consecutive processing units necessary to deliver the meaning of the sentence, the first of which we have already studied with regard to I p and the linguistic I-channel [1][2][3][4][5][6][7][8].…”
Section: Short-term Memory Capacity Can Be Estimated From Literary Textsmentioning
confidence: 99%
See 3 more Smart Citations